A Tumor Microenvironment Responsive Nanotheranostics Agent for Magnetic Resonance Imaging and Synergistic Photodynamic Therapy/Photothermal Therapy of Liver Cancer - Zhu, Yuwan; Deng, Mo; Xu, Nannan; Xie, Yingjun; Zhang, Xuewen (Frontiers in Chemistry, 2021)
Surgery is the main treatment of liver cancer in clinic owing to its low sensitivity to chemotherapy and radiotherapy, resulting in its high mortality and recurrence and metastasis rate. It is feasible strategy to constructing tumor microenvironments activated nanotheranostics agent for diagnosis and therapy of liver cancer. Herein, a nanotheranostic agent (MONs@PDA-ICG) with manganese oxide nanoflowers (MONs) as core and ploydopamine (PDA) as shell loading with ICG as photosensitizer and photothermal agent is reported. MONs@PDA-ICGcan not only produce reactive oxygen species (ROS) to kill the cancer cells, but also exhibit good photothermal performance for photothermal therapy (PTT). Importantly, O2 generated by MONs decomposition relieved the tumor hypoxia and further enhanced the treatment effect ofphotodynamic therapy (PDT).In addition, the released Mn2+ ionsmake MONs@PDA-ICG serve as tumor microenvironments responsive MRI contrast for highly sensitive and specific liver cancer diagnosis.